ANALISIS USER SATISFACTION TERHADAP VIRTUAL TOUR INTERAKTIF PADA CLUSTER D'ROYAL VILLAGE MENGGUNAKAN METODE SYSTEM USABILITY SCALE (SUS) TERINTEGRASI ISO/IEC 25010 - Ernisya Emilya; Faiza Rini; Rahayu Trisetyowati Untari (Smart Education, 2026)
Abstract: The development of digital technology encourages the use of virtual tours as an interactive promotional medium in the property sector. This study aims to analyze the level of user satisfaction with the web-based virtual tour at D'Royal Village using the System Usability Scale (SUS) method reinforced with usability aspects based on the ISO/IEC 25010 standard. The study used a descriptive quantitative approach with 30 respondents selected through purposive sampling. Data were collected using the SUS questionnaire and additional statements representing the sub-characteristics of appropriateness recognizability, user interface aesthetics, and operability. The results show an average SUS score of 77.50 (Acceptable, Grade B,